Beyond HDI: Maqasid Welfare Diagnostics in a Low-HDI Muslim District - Ahyak; Sulhan (Social Science Academic, 2025)
Conventional human development measurement remains important for evaluating regional progress, yet it may not fully capture ethical, religious, familial, and intergenerational dimensions of welfare in Muslim-majority contexts. This study aims to construct a Maqasid Welfare Index for Kabupaten Sampang, Indonesia, compare its movement with the Human Development Index (HDI), and identify welfare dimensions that remain less visible in aggregate human development measurement. Using an exploratory quantitative case-study design, the study analyses district-level secondary data from 2021 to 2024. The Maqasid Welfare Index was constructed through min–max normalisation and equal weighting across five maqasid dimensions: religion, life, intellect, lineage, and wealth. The findings show that HDI and the Maqasid Welfare Index moved in the same positive direction during the observation period. However, dimensional disaggregation reveals that welfare progress was uneven, with the lineage and family dimension remaining relatively weaker than the other maqasid dimensions. The strong association between HDI and maqasid-based welfare is interpreted as statistical co-movement rather than causal evidence. The study concludes that maqasid-based welfare measurement can serve as a diagnostic complement to HDI by revealing hidden welfare imbalances in low-HDI Muslim-majority regions.